KNOWLEDGE AND PERCEPTIONS OF PHARMACY STUDENTS TOWARD TELEPHARMACY SERVICES IN SOUTH KALIMANTAN, INDONESIA - Eko Yatminto; Nanang Munif Yasin; Chairun Wiedyaningsih (Journal Pharmaceutical Science and Application, 2025)
Background: Telepharmacy offers a promising solution to improve access to pharmaceutical care in remote regions such as South Kalimantan, Indonesia. However, research on pharmacy students’ knowledge and perceptions of telepharmacy remains limited, even though their perspectives are crucial for the digital transformation of pharmaceutical services. Objective: This study aimed to assess pharmacy students’ knowledge and perceptions of telepharmacy in South Kalimantan and to identify associated factors. Methods: A cross-sectional online survey was conducted among 453 pharmacy students from six universities in South Kalimantan (October–December 2024) using a validated 40-item questionnaire. Knowledge and perception scores were categorized by sample medians, and non-parametric statistical analyses were performed using SPSS version 27. Results: Overall, 58.7% of participants had high telepharmacy knowledge, indicating a moderate regional knowledge level, and 54.3% reported positive perceptions. Knowledge was significantly associated with academic year (p < 0.001), parental education (p = 0.014), and university type (p < 0.001), while perceptions were influenced by age (p < 0.001), academic year (p < 0.001), parental education (p = 0.009), and healthcare work experience (p = 0.027). No significant correlation was observed between knowledge and perception scores (ρ = 0.089, p = 0.058). Conclusion: Pharmacy students in South Kalimantan exhibited moderate knowledge and generally positive perceptions of telepharmacy, but these domains were not significantly correlated. The findings underscore the importance of standardized telepharmacy education, integration of practical training, and stronger emphasis on regulatory and data-security aspects to strengthen readiness for digital healthcare transformation.